Sound transmission through ceilings from air terminal devices in the plenum - Warnock, A.C.C. (Canadian Acoustics, 1998)
HVAC sources in ceiling plenums are often major contributors to the noise level in occupied spaces below. A study was conducted to determine the sound attenuation through ceiling systems and the sound pressure levels in the room below. The focus of the study was on the interactions between terminal units, the ceiling panels, the plenum and the room below. The intent was to evaluate the calculation methods in ARI 885-90 and suggest improvements when necessary. Results showed that the difference between the sound power of a given device placed in the plenum and the average pressure level in the room below measures the combination of the plenum/ceiling effect and the average space effect.